INCOME OF WORKERS IN THE AGRICULTURAL SECTOR IN BRAZIL AND IN THE CENTRAL-WEST REGION: AN ANALYSIS BASED ON THE THEORY OF SEGMENTATION - Alan Santos; Priscila Casari (Redes, 2014)
The aim of this paper is to evaluate the difference in earnings of workers in the production of some agricultural commodities and workers in other crops in Brazil and in the Central-West region. It is mainly used the labor market segmentation theory, and references on the human capital theory and the agricultural labor market. Data from the National Sample Survey of Households (PNAD-IBGE) of 2009 is used to present descriptive statistics on income and socioeconomic characteristics of workers, and to estimate a mincerian earnings equation, by the method of robust least squares. Soy, corn, sugar cane, and meat whore chosen to represent de agricultural commodities group. The results show that even controlling for the effect of human capital, there is differential in earnings for workers in commodity production in Brazil and in the Central-West region, indicating that the agricultural labor market is segmented.